Cost-effective fabrication of graphene-like nanosheets from natural microcrystalline graphite minerals by liquid oxidation–reduction method. Issue 51 (22nd June 2017) - Xie, Wei; Zhu, Xukun; Xu, Shang; Yi, Shihe; Guo, Zhanhu; Kuang, Jiacai; Deng, Yingjun
Abstract : Graphene-like nanosheets were fabricated using natural microcrystalline graphite minerals (NMGM) instead of flake graphite (FG) using a liquid oxidation–reduction method. Abstract : It is a challenge to prepare graphene-like nanosheets (GNs) with desired electrical properties from natural microcrystalline graphite minerals (NMGM) since the impurities in NMGM are always hard to eliminate and the grain size of NMGM is much smaller than that of flake graphite (FG). The morphology, structure, surface chemistry, and compositions of the GNs prepared from NMGM using a liquid oxidation–reduction approach were investigated in this study. GNs with layer number ranging from 3 to 7, thickness of 1.1 nm, and sizes up to 1 μm × 2 μm were obtained and confirmed from scanning electron microscopy, transmission electron microscopy and atomic force microscopy images. The results of Fourier transform infrared spectroscopy and X-ray photoelectron spectroscopy analysis show that, during the whole fabrication process, the generation and elimination of oxygen-containing groups or reestablishment of the conjugated graphene network occur. The results of Raman spectroscopy and X-ray diffraction measurements show that the GNs possess an amorphous nanostructure. The as-produced GNs with adjustable electrical resistivity can be easily transferred into well distributed bulk materials by freeze-dried strategy. This cost-effective synthesis strategy of GNs from abundant NMGM provides great potential for the commercialization of GN production.